Pengaruh Profitabilitas Terhadap Harga Saham Perusahaan Sub Bagian Pertambangan Batu Bara yang Terdapat Di Bursa Efek Indonesia Periode Tahun 2018-2022 - marnaresya, prety; rismansyah, rismansyah; Akila, Akila (Jurnal Ilmiah Wahana Pendidikan, 2023)
This study aims to determine the effect of profitability simultaneously or partially on stock prices in coal mining sub-division companies listed on the Indonesia Stock Exchange for the 2018-2022 period. The method used in this research is to use a deductive quantitative method. The population in this study are Coal Mining Sub-Division Companies listed on the Indonesia Stock Exchange for the 2018-2022 period with a total of 28 Coal Mining Sub-Division Companies. The sample in this study was 10 companies of the Coal Mining Sub-Division with the sampling method using purposive sampling. In this study, researchers used data analysis techniques including the classical assumption test, multiple linear regression tests and hypothesis testing using the SPSS version 26 application. The results of this study indicate that based on the t-test or partially the three variables, namely Return On Assets (ROA), Return On Equity (ROE), and Net Profit Margin (NPM) have a significant influence on stock prices, then based on the F-test which is equal to 0.003 <0.05 means simultaneously the ratio of ROA (Return On Assets), ROE (Return On Equity) , and NPM (Net Profit Margin) have a significant influence on stock prices